The establishment and spread of the stem‐boring weevil Listronotus setosipennis (Coleoptera: Curculionidae) released against the invasive weed Parthenium hysterophorus L. (Asteraceae) in Ethiopia. Issue 3 (10th August 2021) - Mersie, Wondi; Amare, Tesfay; Chala, Lidya Alemayehu; Negeri, Mulugeta; McNamee, Clyde
Abstract: The establishment and spread of the stem‐boring weevil, Listronotus setosipennis (Coleoptera: Curculionidae) released in 2017 for the control of the invasive weed, Parthenium hysterophorus (L.) (Asteraceae) at four locations in northeastern Ethiopia were assessed over a 4‐year period. The number of L. setosipennis eggs on parthenium in 0.5 m × 0.5 m quadrats was recorded at each location where the weevil was originally released and where it spread later. The weevil damage to parthenium and the distance it spread were also recorded. At all release locations, the number of L. setosipennis eggs detected increased over the 4‐year assessment period indicating the build‐up of the weevil population where it was released. At one of these locations, Chorisa, the number of eggs increased from 2.7 ± 1.3 m −2 in 2017 to 92 ± 6.1 m −2 in 2020. Similarly, at the site where the weevil spread (dispersal site), the number of L. setosipennis eggs detected on parthenium rose over the 4‐year period. L. setosipennis larvae damage to parthenium was evident at all release locations ranging from 13.3 ± 3.3% to 36.7 ± 6.7%. Similar level of damage (36.7 ± 5% to 66.7 ± 8.3%) was also recorded at the dispersal sites. After 4 years, the maximum distance L. setosipennis spread from its original release spots was 185.3 ± 12.0 m. The establishment and spread of the weevil were slow but was steady at all locations in northeastern Ethiopia.